Thermodynamic study of a novel trigeneration process of hydrogen, electricity and desalinated water: The case of Na-O-H thermochemical cycle, SCWR nuclear power plant and MED desalination installation. (1st April 2020) - Marques, João G.O.; Costa, Antonella L.; Pereira, Claubia
Highlights: A trigeneration process of H2, electricity and desalinated water was proposed and studied. It is based on the technologies Na-O-H cycle, SCWR power plant and MED desalination. Mass, energy and exergy balances are applied to evaluate trigeneration thermal performance. EES software was used to model the studied systems. Such process has potential to produce 5 kg/s of H2, 400 MWe and 980 kg/s of H2 O. Abstract: Hydrogen (H2 ) is a substance with a wide range of applications, especially ammonia (NH3 ) production. It is the key chemical used to make fertilizers, a pillar of agriculture industry, an important activity for society. H2 can be obtained according to different processes, including the recent method Na-O-H (sodium-oxygen-hydrogen) thermochemical water splitting cycle that produce it by cracking H2 O (water) molecules into H2 and O2 (oxygen) through cyclic chemical reactions based on the elements Na, O and H. Such reactions are sustained by a heat source at specified temperature level. In this context, nuclear reactors, such as Supercritical Water Reactor (SCWR), are suitable energy options for this kind of process because they are designed to support electricity together with high temperature applications like H2 production. At the same time, water could be get by means of MED (Multi-Effect Distillation), a desalination method able to harvest waste heat from thermal systems. This approach allows saving the available potable water to be used in essential human needs such as drinking and agriculture while the desalinated one would serve as hydrogen source in the sodium-oxygen-hydrogen technique. Then, H2 production based on the technologies Na-O-H cycle through the heat supplied by SCWR coupled to a MED unit enables the trigeneration of electricity-hydrogen-water, three important goods for current society, what justifies the development of a paper covering this multigeneration approach. So, the main aim of this work is to evaluate the thermodynamic performance of this trigeneration case, a task never done before because those three systems were not coupled together aiming this multigeneration case as it was checked in the literature. It was considered a SCWR with output thermal power equal to 1000 MWth as the heat source to both Na-O-H hydrogen production facility plus MED installation. The work is developed by implementing mass and energy balances in Engineering Equation Solver (EES) software to determine the amount of H2, electricity and desalinated H2 O acquired. According to the main results, this trigeneration process has potential to produce a maximum of 5 kg/s of hydrogen, 400 MW of electricity and 960 kg/s of desalinated H2 O.